(untitled) (Bangladesh Journal of Anatomy, 2014)
A young male who had history of ingestion of methanol developed severe anorexia, nausea, and profuse vomiting after a short period. After evaluation he was found to develop severe renal failure, metabolic acidosis & dyselectrolemia. He was given haemodialysis for several sessions. Few days later he developed weakness and blurred vision. Neurological evaluation showed toxic neuropathy. In spite of giving haemodialysis near about three months his renal function did not improved. Renal biopsy showed features suggestive of acute cortical necrosis. He was declared a case of End Stage Renal Disease (ESRD) & an arterio-venus fistula was created in his left forearm for maintenance of haemodialysis DOI: http://dx.doi.org/10.3329/bja.v11i1.20508 Bangladesh Journal of Anatomy, January 2013, Vol. 11 No. 1 pp 44-47